Midcrustal Deformation in the Central Andes Constrained by Radial Anisotropy. Issue 6 (4th June 2018) - Lynner, Colton; Beck, Susan L.; Zandt, George; Porritt, Robert W.; Lin, Fan‐Chi; Eilon, Zachary C.
Abstract: The Central Andes are characterized by one of the largest orogenic plateaus worldwide. As a result, they are home to some of the thickest continental crust observed today (up to ~75‐km thick). Understanding the response of the crust to such overthickening provides insights into the ductile behavior of the midcrust and lower crust. One of the best tools for examining crustal‐scale features is ambient noise tomography, which takes advantage of the ambient noise wavefield to sample crustal depths in great detail. We extract Love and Rayleigh wave phase velocities from ambient noise data to invert for V sh, V sv, and radial anisotropy throughout the Central Andes. We capture detailed crustal structure, including pronounced along‐strike isotropic velocity heterogeneity and substantial (up to 10%) radial anisotropy that varies with depth. This crustal anisotropy may have several origins, but throughout the majority of the Central Andes, particularly beneath the Altiplano, we interpret radial anisotropy as the result of mineral alignment due to ductile crustal deformation. Only in the strongly volcanic Altiplano‐Puna Volcanic Complex is radial anisotropy likely caused by magmatic intrusions. Key Points: The midcrust throughout the Central Andes is characterized by positive radial anisotropy resulting from ductile crustal flow Ductile crustal flow in the Central Andes extends to at least 40 km depth and may extend deeper We observe very strong positive radial anisotropy in the APVC likely due to a horizontally layered magmatic storage system